The Relationship Analysis Between Husband’s Knowledge, Attitude And Practice for Maternal Health - Novina Eka Muji; Arief Hargono (Jurnal Berkala Epidemiologi, 2014)
Pasuruan district was one of many areas which capable to decrease Maternal Mortality Ratio (MMR) up to the targeted level number by MDGs 2015. Maternal health was also one of the husband’s duties as a decision-maker in the family. The purpose of this research was to analyze a relationship among knowledge, attitude and the husband’s practice for maternal health. This research was done in May until June 2013 at Puspo sub-district of Pasuruan District. A research design was a cross sectional of the population from all of the couples who had a child from the second month to 2 years old, lived in a roof. The total of respondent was 115 couples. The sample selection was systematically done by random sampling. The variable of this research was characteristic, knowledge, attitude and the husband’s action. The result showed that most respondents had lower knowledge about maternal health (72,2%), a positive attitude (73,9) and the unsupported action in maternal health (68,7). A chi-square test showed that there was no relationship between knowledge and action, neither between attitude nor action on maternal health. The conclusion of this research was there is no correlation between knowledge and attitude of the husband with the husband in the act of giving support to maternal health became pregnant wife until the election of contraception.